The Solubility of Tugarinovite (MoO2) in H2O at Elevated Temperatures and Pressures. (18th December 2017) - Saha, Pritam; Anderson, Alan J.; Lee, Thomas; Klemm, Matthias
Abstract : The solubility of tugarinovite (MoO2 ) in pure water was investigated at temperatures between 400 and 800°C and at pressures ranging between 95 and 480 MPa by using in situ synchrotron X-ray fluorescence (SXRF) to separately analyze high temperature aqueous solutions in a hydrothermal diamond anvil cell (HDAC). The concentration of molybdenum in the fluid at 400 and 500°C was below detection; however, at temperatures between 600 and 800°C, the solubility of tugarinovite increased with increasing temperature by two orders of magnitude. The molybdenum concentration at 600°C and 800°C is 44 ppm and 658 ppm, respectively. The results complement the data of Kudrin (1985) and provide the first measurement of MoO2 solubility at pressure and temperature conditions comparable to intrusion-related Mo deposit formation. The data are also relevant to the study of water chemistry and corrosion product transport in supercritical-water-cooled reactors, where Mo-bearing steel alloys interact with aqueous solutions at temperatures greater than 600°C. The application of in situ SXRF to solubility measurements of sparingly soluble minerals is recommended because it circumvents analytical uncertainties inherent in determinations obtained by quenching and weight loss measurements.